A Study of Examination System of AICTE - Garg, Shiv Kumar; Sharma, A. K (Journal of Commerce and Trade, 2009)
Since last two decades, hurried expansion of technical institutions in India has resulted in deterioration in quality of technical manpower coming out from these institutions on account of poor infrastructure, admission policy and above all the examination system adopted by these institutions. Decline in quality of technical education is evident from the fact that a sizeable segment of the qualified engineers seriously lack in communication skill, experimental skill, mathematical skill, analytical skill and problem solving skill. Quality problems in the examination system in general have been analyzed. Thorough overhaul in the examination system with regard to its policies, procedures and practices have been suggested. Statistical analysis of the examination results has been suggested for identifying the problems in the examination saystem as well as in the teaching process of a university. Other remedial measures have also been suggested to make the examination system more efficient in order to produce technical manpower of superior quality.